Text Digital Teaching Materials Negotiation Oriented Adab Speak For Class XS MA Siswa Students - Ihrom Maulana; Jaja Jaja; Abdul Rozak (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Language is a communication tool used by humans to express ideas or ideas. The use of language in communication must pay attention to politeness so that there is no dispute with the speech partner. Education as the key to the formation of knowledge and personality is a solution to build politeness in students' language competence. Solutions that can be built to improve students' language politeness through the learning process. This research was conducted to improve students' language politeness by linking negotiation text learning materials to X grade high school students. The resulting product is digital teaching materials with the orientation of student-speaking etiquette. Researchers create digital teaching materials with the Heyzine Flipbooks digital application Research stages 1) Data analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation of the results of teaching materials products. Data analysis was carried out by analyzing the data on the need for digital teaching materials and analyzing the negotiating text that would be included in the teaching materials. The design of digital teaching materials is oriented towards spoken etiquette which is validated by material and media experts. Experiment with educators and students in the process of learning activities. The results of the research implementation show that the digital negotiating text teaching materials are valid and feasible to use. Evaluation of the results of the product of digital teaching materials for negotiating texts is able to improve students' speaking manners because they have aspects of language politeness.